Strategic technological innovation for sustainable development. (2016) - Shrivastava, Paul; Ivanaj, Silvester; Ivanaj, Vera
Technological innovation can be highly instrumental in achieving sustainable development. How well does technology innovation research address the needs of sustainable development and in what directions does this research need to move to usher in sustainable development? We use co-word analysis in existing research publications to map the intellectual structure of the field of 'strategic technological innovation for sustainable development' during the period 1989-2009. The results suggest a list of 26 different research themes. Certain research themes are considered to be central and represent coherent and well-developed concepts. Other themes have arisen, matured, and then faded as major research concepts. Some other themes seem to be emerging or immature, but they signal the appearance of new research areas that are becoming central. Finally, there are some areas that are peripheral and others that need further development. We propose an integrative framework to study strategic technological innovation for sustainable development.